PERTUMBUHAN KREDIT DAN TINGKAT KEBERISIKOAN BANK - Chorry Sulistyowati (Jurnal Manajemen Indonesia, 2015)
Bank is one of financial institution which has strategic role in the economy. Bank has to deliver funds from surplus unit to deficit unit. Prudential banking helps bank to minimize the risk especially credit risk. Loan growth and riskiness of the bank are the important thing for bank profitability and bank solvency. This research aimed to measure the effect of loan growth to bank profitability and bank solvency. Data used in this research collected from Financial Annual Report Bank Indonesia (BI) from 2008 to 2013 with multiple linear regression. The result from this research are either loan growth or size have negative effect to interest revenue only size has significant effect. Second hypothesis also proved that loan growth and size also have negative effect to bank solvency. Both of them are not siginificant